2017
DOI: 10.1111/ddg.13278
|View full text |Cite
|
Sign up to set email alerts
|

Acne

Abstract: Summary Acne is a chronic disease with a high prevalence among adolescents. Key pathogenetic factors (and their clinical correlates) are increased sebum production (seborrhea), follicular hyperkeratosis (comedones), and perifollicular inflammation (papules and pustules). The disease is modulated by a variety of endogenous (androgens, IGF‐1, neuroendocrine factors) and exogenous (Propionibacterium acnes, diet, friction, ingredients of medical or cosmetic topical products) triggers. Acne is associated with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…The occurrence of acne naturally correlates with age and mainly affects people during adolescence . In line with this, we found that acne commonly affected the 18–39 years age groups (23.7%), which underlines the representative nature of the examined population.…”
Section: Discussionsupporting
confidence: 86%
“…The occurrence of acne naturally correlates with age and mainly affects people during adolescence . In line with this, we found that acne commonly affected the 18–39 years age groups (23.7%), which underlines the representative nature of the examined population.…”
Section: Discussionsupporting
confidence: 86%
“…In this way, the hormonal effect on sebum secretion is a key to the pathogenesis of acne. [12][13][14][15][16] During puberty, alteration of the sebum component, called dysseborrhea, stress, irritation, cosmetics, and potential dietary factors lead to the formation of acne lesions. 16 Changes in sebum secretion are considered to be an important factor of acne.…”
Section: Introductionmentioning
confidence: 99%
“…Acne vulgaris affected approximately 80% of patients between 12 and 25 years old without regard to differences in sex and ethnicity (Goh et al, 2019). While the onset of AV varies across age groups, it commonly occurs during puberty and young adulthood and tends to decrease with increasing age (Gollnick, 2015;Wolkenstein et al, 2018); however, persistent and late-onset acne can occur in some patients, for whom acne persists until the fourth and the fifth decade or has its initial onset at an advanced age, respectively (Degitz & Ochsendorf, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Acne vulgaris is characterized by pleomorphic lesions, including comedones, papules, pustules, nodules, and cysts, which appear in the predilection area. It most frequently appears on the face, neck, shoulders, upper arms, upper chest, and upper back, as well as in other areas that contain sebaceous glands (Degitz & Ochsendorf, 2017). While self-recovery can be observed in clinical settings, the sequelae can be lifelong with complications of scar formation (Goh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%